2016
DOI: 10.1016/j.ijbiomac.2016.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and cytotoxicity evaluation of colloidal chitosan – silver nanoparticles – fluoride nanocomposites

Abstract: The present study aimed to evaluate the antimicrobial activity and cytotoxicity of colloidal chitosan - silver nanoparticle - fluoride nanocomposites (CChAgNpFNc), with different silver nanoparticle shapes and sizes. The syntheses of CChAgNpFNc were performed with silver nitrate added to a chitosan solution, addition of a sodium borohydride solution and solid sodium fluoride. Solution of ascorbic acid was added to synthesize larger silver nanoparticles. CChAgNpFNc obtained: S1- 100% spherical, 8.7±3.1nm; S2- 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 36 publications
4
33
0
1
Order By: Relevance
“…In addition, AgNPs/chitosan materials could promote wound healing. 3,17,[28][29][30] In comparison with long-chain high molecular weight chitosan, the short-chain LMWC is better in terms of water solubility and biocompatibility. Besides, it has been confirmed that LMWC enhances the physical and chemical stability of many drugs such as insulin 31 and siRNA, 32 and works as a suitable carrier for the delivery and controlled release of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AgNPs/chitosan materials could promote wound healing. 3,17,[28][29][30] In comparison with long-chain high molecular weight chitosan, the short-chain LMWC is better in terms of water solubility and biocompatibility. Besides, it has been confirmed that LMWC enhances the physical and chemical stability of many drugs such as insulin 31 and siRNA, 32 and works as a suitable carrier for the delivery and controlled release of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Because the oral cavity is an active ecosystem usually colonized by various pathogenic microorganisms, dental materials and implants have an increased risk of contamination and subsequent colonization processes [ 155 ]. In terms of superior antimicrobial activity, promising results were reported with respect to the incorporation of silver-based nanosystems within adhesive resins [ 156 , 157 ], orthodontic cements [ 158 , 159 ], and dental composites [ 160 , 161 , 162 ]. In addition to being used as antimicrobial filling agents within multifunctional biomaterials, another attractive and challenging dental application of AgNPs relies on their potential use as biostatic or biocide coatings for conventional titanium-based dental implants [ 163 , 164 ].…”
Section: Silver Nanoparticles For Dental Applicationsmentioning
confidence: 99%
“…The result showed that the cell inhibition was below 25% at the presence of 20 lg/mL AgNPs ( Figure 5). Freire et al [32] thought that colloidal chitosan-silver nanoparticle-fluoride nanocomposites were non-toxic at a concentration of 50 mg/mL, since in their presence, the RAW 264.7 cell inhibition was below 50%. According to their report, our result indicated that AgNPs from levan are able to display antibacterial activity without being harmful to macrophages.…”
Section: Antibacterial and Cytotoxic Activity Of Agnpsmentioning
confidence: 99%